2005
DOI: 10.1108/09556220510581254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drape characteristics in fabrics

Abstract: PurposeTo provide researchers with the details of developments in instruments to measure fabric drape and review the literature related to fabric drape.Design/methodology/approach – In recent years, there has been a renewed interest in investigating the aesthetic behavior of fabrics due to the developments in objective evaluation techniques. To understand drape behavior, it is essential to know how drape is measured quantitatively. This paper reviews research related to drape characteristics of fabrics, two‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Two-dimensional draping means that the fabric folds under the influence of gravity in one plane, and three-dimensional draping means that fabric deforms forming the folds in more than one plane under the pressure of its own mass [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional draping means that the fabric folds under the influence of gravity in one plane, and three-dimensional draping means that fabric deforms forming the folds in more than one plane under the pressure of its own mass [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kenkare and May-Plumlee used the number and dimensions of nodes as alternative parameters to drape coefficient to quantify drape [49].…”
Section: 6mentioning
confidence: 99%
“…Therefore, it was evaluated subjectively in the textile and apparel industry. Subjective assessments of fabric drape lack reproducibility and often cause controversy due to large variation in evaluators' perception and skill, this shortage ended with development of the quantitative measurement of drape [46,49]. Subjective assessment was affected by individual preference, fashion trends [131] and the length of fabric on the pedestal (sample diameter) [114,132].…”
Section: Effects Of Unbalanced Seamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabric drape is influenced not only by fabric factors but also by their complex interactions. Although extensive information of 2-D fabric drape characteristics can be obtained from instrument measurement, Kenkare and Plumlee (2005) suggested that study of the drape characteristics of complex forms requires drape measurement not only on 2-D fabrics, but also on garments since other factors such as construction methods of clothing also affect the drape. The majority of research on draping has been focused on the draping characteristics of 2-D nonseamed fabrics and the fabric properties affecting them.…”
mentioning
confidence: 99%